DETERMINAN NILAI PERUSAHAAN : KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, DAN KEBIJAKAN HUTANG. - Kusumawati, Rita; Nurafiati, Lasty (STIE Muhammadiyah Tanjung Redeb, 2019)
The purpose of this research is to determine the effect of managerial ownership, institutional ownership, dividend policy, and debt policy on the firms value. Object of this research is used the manufacturing sector listed in Indonesian Stock Exchange (IDXI) in the period 2011-2016. Samples was selected by  purposive sampling method with 104 samples. The data analysis technique of this research using multiple regression analysis with E-Views 7 program.The result  showed that managerial ownership and institutional ownership has positive significant effect on the firm’s value, debt policy has negative significant effect on the firms value, and dividend policy has no significant effect on the firm’s value